Regional Injection of CAR-T Cells for the Treatment of Refractory and Recurrent Diffuse Large B Cell Lymphoma: A Case Report - Wei, Yan-Hui; He, Yu-Zhuo; Lin, Xiao-Yan; Ren, Fu-Xian; Zhu, Hong-Bin; Cheng, Ying; Nan, Zhen; Liu, Zheng-Biao; Yu, Jing-Ya; Guo, Xue-Jun (Frontiers in Cell and Developmental Biology, 2020)
Background Lymphoma is a common hematological malignancy with many subtypes and considerable heterogeneity. Traditional treatments include chemotherapy, radiotherapy, and surgery. Patients with relapsed, refractory or advanced stage lymphoma have a dismal prognosis. In recent years, chimeric antigen receptors (CARs) have been recognized as powerful tools that redirect antigen-specific T cells independent of human lymphocyte antigen (HLA) restriction and specifically kill tumor cells. Satisfactory results with CAR-based treatments have been achieved in relapsed/refractory B cell leukemia/lymphoma. Our center explored the strategy of subcutaneous injections combined with intravenous drip to overcome certain issues. Case presentation A patient with stage IV refractory and relapsed diffuse large B cell lymphoma was treated with regional and intravenous CAR-T cells. During the observation period, the temperature of the skin at the abdominal wall mass was slightly elevated, and tolerable pain in the injection area was reported. Imaging showed regional liquefactive necrosis. After the sequential administration of ibrutinib and venetoclax, the abdominal wall mass significantly decreased in size. Conclusion The regional injection of CAR-T cells might be safe and feasible for the treatment of regional lesions in patients with refractory and relapsed advanced lymphoma.